Emergent Disability and the Limits of Equality: A Critical Reading of the UN Convention on the Rights of Persons with Disabilities - Ribet, Beth (2014)
The UN Convention on the Rights of Persons with Disabilities marks a shift in international legal relationships to, and conceptions of, disability. The Convention is the first binding international instrument of its kind related to disability. Its premises differ from the earlier World Programme on Disability, and more closely integrate the frameworks of U.S. domestic equal protection and disability civil rights law. Drawing on critical race and feminist theory, this Article critically examines the implications of internationalizing a U.S. disability law framework, with particular attention to the problem of emergent disability, or disability which is specifically produced as a consequence of social inequity or state violence